Skew Polynomial Extensions over Zip Rings - Wagner Cortes (International Journal of Mathematics and Mathematical Sciences)
In this article, we study the relationship between left (right) zip property of 𝑅 and skew polynomial extension over 𝑅, using the skew versions of Armendariz rings.